Store depletion-induced calcium influx in rat cerebellar astrocytes - Lo, Kuo-Jung (2002)
1. In rat cerebellar astrocytes, intracellular Ca(2+) store depletion by receptor agonists or sarco(endo)plasmic reticulum Ca(2+) ATPase inhibitors induced a transient increase in the intracellular Ca(2+) concentration ([Ca(2+)](i)) in the absence of extracellular Ca(2+) and a sustained increase in its presence. 2. After 10 min treatment with thapsigargin, the [Ca(2+)](i) was unaffected by removal of thapsigargin, but fell rapidly to the basal level when extracellular Ca(2+) was removed, suggesting the involvement of capacitative Ca(2+) entry (CCE); this effect was not seen until cells had been exposed to thapsigargin for at least 2 min. 3. Using the whole cell voltage clamp technique, a 60 – 100 pA inward current was activated by store depletion, the reversal potential ranging from −5 to 0 mV. 4. When extracellular Na(+) was isotonically replaced by Tris, the thapsigargin-induced [Ca(2+)](i) increase was enhanced, while the inward current was reduced, indicating that store-operated Ca(2+) channels were permeable to Na(+); however, they were not permeable to Sr(2+) or Ba(2+). 5. Thapsigargin-induced CCE remained the same in the presence of nifedipine, La(3+) or Cd(2+), while it was inhibited in the presence of SK&F96365. 6. In cerebellar astrocytes, inhibition of protein serine/threonine phosphorylation promoted CCE. 7. In conclusion, in rat cerebellar astrocytes, store depletion activated a CCE via channels which were permeable to Ca(2+) and Na(+) and regulated by phosphorylation.